Zdrowie i choroba jako awers i rewers ludzkiego życia. Spotkanie biblioterapii aktywnej z autotransgresją Józefa Kozieleckiego w jego autobiograficznej opowieści "Wspomnienia z białego piekła" = Health and sickness as the observe and the reverse of human life. The meeting of an active bible-therapy with ? in an autobiographic story of Józef Kozielecki "The reminiscing from the white hell" - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the view of the polish psychologist on sickness and heath. Anastazja Seul`s writing begins with prior identification of the terms that precedes theoretical presentation of the basis of the bible-therapy. With this as the background were presented autobiographic memoirs of Kozielecki as a type of active bible-therapy. This theoretical part is accompanied by practical part: an analysis of the literary text. It encompasses three areas of auto-surpassing: an intellect, emotions, and will. The analysis reveals auto-therapeutic value of Kozielecki`s memoirs and highlights pro-health meaning of his rebelion against the sickness itself. The dissent for a sickness became the source of his strength in his struggles to become healthy again.
Keywords: Kozielecki, Józef (1936-2017); autobiografia; autotransgresja; biblioterapia; rozwój; aksjologia; autobiography; suffering; bibliotherapy; development; aksjology